RURAL INFRACTIONS: The temporary agrarian workers of Tamaulipas (Mexico) and Andalusia (Spain) - Izcara Palacios, Simón Pedro (Libros UAT, 2018)
This work analyzes, in a comparative way, the socio-labor situation of the agricultural day laborers in Tamaulipas and Andalusia. The first part of the book addresses the problem of orange pickers, both migrants and locals, employees in the central area of ??Tamaulipas, whose socioeconomic situation is characterized by irregular work and underemployment; It also examines the social and labor conditions of Tamaulipas rural migrants employed irregularly in American agriculture. The second part of the book analyzes the social situation of Andalusian agricultural temporary workers, characterized by a situation of quasi-permanent unemployment and a strong dependence on unemployment benefits; In addition, it studies the problems of Moroccan workers employed surreptitiously in intensive Andalusian agriculture. Casual agricultural workers in both Tamaulipas and Andalusia face the same problems of underemployment, unemployment, precarious living conditions and deep-rooted feelings of marginality and frustration. International migrant workers irregularly employed in agriculture, both Tamaulipan rural workers in the United States and Maghrebi day laborers in Andalusia, suffer from the same problem of social isolation and lack of interaction with the indivuduals and institutions that represent society. These elements allow describing the social groups analyzed in this work under the concept of "infraclases".